Density-controlled carbon nanotubes - Hsu, CH; Chen, CF; Chen, CC; Chan, SY (My University, 2005)
We demonstrate that the field emission efficiency was greatly improved by reducing the density of carbon nanotubes (CNTs). In this study, catalyst composed of gold and nickel was deposited by e-gun evaporation before pre-treatment of furnace annealing. Carbon nanotubes were then gown on silicon substrate using bias-assisted microwave plasma chemical vapor deposition. Vertical aligned carbon nanotubes were grown with gas mixture of methane and hydrogen under external DC bias. The surface morphology and the tubular structure of carbon nanotubes were confirmed by electron microscopy and the density of carbon nanotubes could be controlled by the composition of the catalyst. The field emission properties were investigated through I-V measurement and the effects are discussed. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: carbon nanotubes; field emission; microwave plasma chemical vapor deposition; screening effect